Measure of Central Tendency: Undergraduate Students’ Error in Decision-Making Perspective - Rosidah, Rosidah; Ikram, Fadhil Zil (International Journal of Education, 2021)
The purpose of this research was to examine undergraduates' understanding of the central tendency measure from a decision-making perspective. The research adopted a qualitative method by employing an interview and test to obtain the data.  It enrolled 93 undergraduate students who had previously studied basic statistics and applied statistics. Four students were selected for interviews out of the 93 participants. The analysis model used included data condensation, data visualization, and conclusion and verification. A large number of students were unable to provide explanations for their decisions. The majority of students related the test with the necessity of calculating an average or selecting a more straightforward measure. None of the students was aware of the presence and effect of outliers in the data. The undergraduate students demonstrated a lack of awareness of the factors that could influence their decision-making. The students did not consider other variables. The majority of them were unaware of the benefits and drawbacks of using mean, median, and mode to describe data.